Issues Of Ensuring Food Security Under Climate Change Conditions - Saidova Dildora Nurmatovna; Nasulloyeva Malika Botir qizi (Zien Journals, 2025)
Sharp climate changes pose serious risks such as reduced water resources, an increase in natural disasters, and a decline in agricultural productivity, which altogether hinder the sustainable development of our region. These consequences primarily have a negative impact on vulnerable segments of the population
Keywords: environment; biodiversity; climate change; decarbonization